NONVERBAL CREATIVITY IN TECHNICAL EDUCATION AND ITS INFLUENCE ON THE SCHOOL MANAGEMENT - HONZIKOVA, Jarmila (Journal of Technology and Information Education, 2010)
This article deals with the research of creative skills within the project Nonverbal creativity in technical education carried out within the scope of grant GACR 406/07/0109. This project deals with the research of nonverbal creativity and at the same time it will try to show how to develop the creativity in technically oriented subjects at work with the school education programme.
Keywords: technical education; nonverbal creativity